Regime of fluvial phosphorus constituted by sediment - Li, Huali; Zhou, Jianjun; Zhang, Man (Frontiers in Environmental Science, 2023)
Phosphorus (P) is a crucial macronutrient in aquatic systems worldwide, recently turning into a pollutant. Most of P circulates with sediment through rivers, where the sediment concentration and size may vary widely. A general regime by which sediment affects P in rivers with a wide range of sediment concentration and sizes is still lacking. Here, a series of water samples were collected from six rivers in China where the sediment concentration and size distribution vary significantly, and the P properties were analyzed. We derived generalized relationships between sediment and P as follows: (1) a strong positive correlation between total P and sediment concentration is observed, indicating that sediment is a crucial agent in the movement and fate of P; (2) the negative correlation between dissolved P and sediment concentration indicates a buffering effect of sediment, especially fine sediment, on dissolved P. It is further inferred that river damming could cause a P blockage tendency, changing P from nourishment to contamination in rivers. The unified regime for rivers with large differences in the sediment properties gives a reference for global studies on relations between P and sediment. The knowledge is also highly relevant for researches on the fundamental biogeochemical cycle.